A Comparative Study of the Physiological Variables Associated with Cardiovascular Disease Risk Factors Among Retirees in Ile-Ife, Nigeria - Dominic, Olufunmilola L.; Ojo, Israel A.; Adedoyin, Rufus Adesoji (NIU Journal of Social Sciences; Vol 3 No 1 (2017): KIU Journal of Social Sciences, Vol. 3 No. 1, March 2017, 2017)
The study determined cardiovascular disease (CVD) risk factors, assessed Physiological variables and established the relationship between physiological variables and cardiovascular disease risk scores among retirees.  Two hundred and three (203) apparently healthy adults, aged between 54 and 89 years with a mean age of 63.99 Â± 6.70 years participated in the study. One hundred and four (104) retirees and ninety nine (99) age-matched self-employed adults were recruited. The subjects were selected from the Association of Pensioners of ObafemiAwolowo University (OAU) and OAU Teaching Hospitals Complex, Ile- Ife using purposive sampling technique. The control subjects were non-retirees but age-matched adults they were recruited from different shops, workshops and market places within Ile-Ife. Weight, height, waist circumference, systolic blood pressure (SBP) and diastolic blood pressure (SBP) were measured using standard equipment and procedures. The subjects CVD risk scores were measured based on the information from the questionnaire given to them, they were classified into high, medium and low risk based on the scores calculated from the questionnaire.  Both descriptive and inferential statistics were used to analyze the data.The study concluded that the physiological variables; systolic and diastolic blood pressure had significant relationship with the CVD risk scores, that an increase in the value of physiological variables leads to an increase in CVD risk scores, The retirees had significantly higher CVD risk scores than the controls. Keywords: cardiovascular disease, physiological variables, retirees